Plaque Formation by 55 Rhinovirus Serotypes - Fiala, Milan (1968)
Plaque production by 55 rhinoviruses in several lines of HeLa cells is reported. Forty-nine types produced macroscopic plaques under the conditions described previously employing 30 mM MgCl(2) and 30 μg/ml of DEAE-dextran in overlay and M HeLa cells. Basically three kinds of plaques were observed: clear large and intermediate sized plaques and small turbid plaques. Five rhinoviruses produced plaques only in a sensitive clonal line isolated from the M HeLa line. Rhinovirus type 4 produced plaques after the pretreatment of cells with actinomycin D. Enhancement of plaque formation by MgCl(2) has been demonstrated to date with 17 rhinoviruses. Some rhinoviruses were enhanced either by DEAE-dextran or by dextran sulfate in the overlay. No inhibitors were found in any of 10 bovine sera tested. Rhinovirus type 2 was visualized inside HeLa cells by electron microscopy and there appeared to be a very high ratio of physical particles per infectious unit of virus.